Il disgusto nel secolo dei Lumi (Lebenswelt. Aesthetics and philosophy of experience., 2013)
In this essay I try to answer two different questions: ‘how can we define disgust?’ and ‘which kind of relationship is there between taste and disgust?’. In order to give a definition of the notion of disgust I analyze the works of different modern philosophers of the 18th century. In the first part of my writing I support the idea that disgust is strictly connected to the sense of smell. Taking into account this consideration and the idea that aesthetic feeling is never a mere pleasure of sense, I then make a distinction between feeling and emotion. This distinction allows me to say that disgust is always an emotion, and it is never connected to a judgment of taste. Within the experience of disgust, the distance and the disinterest that aesthetics requires are nullified: both in reality and in works of art disgust can never be mixed with pleasure. On this basis, I analyze the connection between disgust and hunger, as discussed by Diderot and Lessing, sympathy and animals. Ultimately, I can state that disgust can never be mixed with pleasure, and it can never find a place in the judgment of taste. Disgust isn’t opposed to beauty, but it marks its limits.